GROIN DESIGN AS A COASTAL PROTECTION PAGATAN BEACH, TANAH BUMBU REGENCY - Holdani Kurdi; Helmy Kurnia; Novitasari Novitasari (Universitas Lambung Mangkurat, 2017)
Damage caused by coastal erosion in Pagatan Beach in Tanah Bumbu regency require strong and stable coastal protection. During these days as coastal protection used groins type of protection are made by gabion wire, which is easily damaged because gabion wire used for this more easily corroded. Therefore, to anticipate it, it should be made a design of a safety coastal structures by groin type in Pantai Pagatan that strong and stable. To calculating the wave height and period used Severdrup Munk Bretschneider (SMB) method which has been modified by the Shore Protection Manual (US. Army Corps of Engineers, 1984). This design refers to the Pd T-04-2005-A. These data are required is wind data, wave data, tide data, sediment data, and soil data. The results obtained dimensional design of the building with a base of 22m width and a crest elevation of 5.5m groin plan, ultimate withstand capacity of 400,128t/m2, overthrown stability 33,836 and shear stability 4,198. Sediment transport that occurs along the coast of 30,107.72m3/day, significant wave height (H33) is 1.98 m and the Design Water Level (DWL) 2.77 m. In this design, material used is crushed stone. Keywords: design, coustal protection, groin, Pagatan Beach.